The vanishing phantoms - Patil, Aniket; Jain, Siddhant; Acharya, Sourya; Gagneja, Sakshi (International Journal of Advances in Medicine, 2019)
A50-year-old known diabetic female presented to us with gradually progressive dyspnea and swelling over both lower limbs since 15 days. She was a known case of ischemic heart disease since 3 years on medical management. On examination she was afebrile, heart rate was 128 beats/min, BP-98/52mm of Hg, JVP was raised at 11 cm of water. The respiratory rate was 30/min. Oxygen saturation was 92% while breathing in ambient air. Air entry was decreased on right inter and infra scapular areas with bi basal late inspiratory crepitations.